2022
DOI: 10.48550/arxiv.2203.13847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cluster Algebras: Network Science and Machine Learning

Abstract: Cluster algebras have recently become an important player in mathematics and physics. In this work, we investigate them through the lens of modern data science, specifically with techniques from network science and machine-learning. Network analysis methods are applied to the exchange graphs for cluster algebras of varying mutation types. The analysis indicates that when the graphs are represented without identifying by permutation equivalence between clusters an elegant symmetry emerges in the quiver exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…It was shown that the cluster algebra mutation rules can be realised as Seiberg dualities of quiver gauge theories, where Seiberg duality is a generalisation of the classical electro-magnetic duality for 4d N = 1 supersymmetric gauge theories, this interpretation is the focus of the work in [33] of which we summarise here. This work is also extended from quiver mutation to cluster mutation in [78].…”
Section: Quivers and Mutationmentioning
confidence: 99%
“…It was shown that the cluster algebra mutation rules can be realised as Seiberg dualities of quiver gauge theories, where Seiberg duality is a generalisation of the classical electro-magnetic duality for 4d N = 1 supersymmetric gauge theories, this interpretation is the focus of the work in [33] of which we summarise here. This work is also extended from quiver mutation to cluster mutation in [78].…”
Section: Quivers and Mutationmentioning
confidence: 99%